2011
DOI: 10.1039/c1ce05185g
|View full text |Cite
|
Sign up to set email alerts
|

The role of brookite in mechanical activation of anatase-to-rutile transformation of nanocrystalline TiO2: An XRD and Raman spectroscopy investigation

Abstract: The mechanism of phase transformation in nanocrystalline TiO 2 powders at ambient temperature during high energy ball milling and the role of brookite phase in anatase-to-rutile phase transformation were investigated by the use of Rietveld analysis of X-ray diffraction patterns and Raman spectroscopy methods. The milling process was performed on a fully anatase phase nanocrystalline TiO 2 powder via a high energy planetary ball mill with different ball-to-powder weight ratios followed by annealing of the as-mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
69
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(82 citation statements)
references
References 29 publications
5
69
0
3
Order By: Relevance
“…The Raman bands located at B142, 194, 394, 513, and 634 cm À1 are attributed to the anatase phase, and the bands located at B141, 237, 447, and 610 cm À1 are assigned to the rutile phase. 17 Raman spectra serve as a further proof that increasing the annealing temperature induces the transition from the anatase to rutile phase. Our previous study 27 addressed the behaviour of titania nanotubes in detail upon annealing under different atmospheres, which confirms the existence of oxygen vacancies inside self-organized TiO 2 nanotubes after annealing under an argon atmosphere.…”
Section: Structural Characterizationmentioning
confidence: 93%
See 1 more Smart Citation
“…The Raman bands located at B142, 194, 394, 513, and 634 cm À1 are attributed to the anatase phase, and the bands located at B141, 237, 447, and 610 cm À1 are assigned to the rutile phase. 17 Raman spectra serve as a further proof that increasing the annealing temperature induces the transition from the anatase to rutile phase. Our previous study 27 addressed the behaviour of titania nanotubes in detail upon annealing under different atmospheres, which confirms the existence of oxygen vacancies inside self-organized TiO 2 nanotubes after annealing under an argon atmosphere.…”
Section: Structural Characterizationmentioning
confidence: 93%
“…Recently, our group has developed new engineered energy devices based on oxygen depleted, highlyordered, self-organized titania nanotubes synthesized via anodic oxidation of titanium foil to overcome the high electrical resistivity of bare titania to meet the requirements for higher specific capacitance applications. For many applications, the crystal phase structure and the size of the particles are the most crucial parameters to alter the surface area and properties of titania, 16,17 resulting in different electrochemical properties. As-synthesized TiO 2 is usually amorphous, which limits its application in many fields.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of milling on the phase transformation of titania with and without dopants has been widely investigated [141][142][143][144][145][146][147][148][149][150][151][152][153][154][155][156] because of the industrial interest in this material as a photocatalyst. It has been generally reported that the anatase -rutile transformation takes place through the intermediate formation of a non-equilibrium high-pressure phase.…”
Section: Oxidic Compoundsmentioning
confidence: 99%
“…Apart from phase identification, Raman characterization is also used for the determination of size and non-stoichiometry of TiO 2 nanocrystals [182,186,[196][197][198][199][200][201], both of which are very important in TSO-related applications. Broadening and shifting of Raman bands are observed when particle dimensions change or oxygen deficiency is induced in the TiO 2 crystal lattice (also, to some extent, strain, non-homogeneity of the size distribution, and anharmonic effects due to temperature increase can contribute to changes in the peak position and shape [182]).…”
Section: Raman Spectroscopymentioning
confidence: 99%